The Blockhouse in Harlingen, Weeshuisstraat 1/3 (Bulletin KNOB, 2003)
On the occasion of the demolition plans for the boarding school of the Noordzeecollege a building-historical research took place in two phases. It was established that the oldest part of the complex was built in 1500, probably as a warehouse building on the blockhouse. The blockhouse was a rectangular fortress measuring approximately 115 x 145 metres with revetted earth ramparts and two round bastions.The bastion on the south-east side was a later addition. Within the fortress there were various buildings around a parade ground. In the Eighty Years' War the blockhouse was dismantled, after which around 1600 the former warehouse building was redesignated as town orphanage. In 1958 the building obtained its present function as boarding school. In the course of time a lot of refurbishments took place, so that at present the building has a primarily I9th and 20th century appearance.On the basis of the research results an evaluation was drawn up, in which e.g. the special historical values of the building as part of the blockhouse were pointed out, the significance of the orphanage for the town of Harlingen and the building-historical values of the walls and the single oak joisting (from 1500). After careful consideration it was decided to maintain the building and convert it into apartments.